FACTOR PREDISPOSING PLAN OF MARRIAGE AMONG YOUTH - Angraini, Wulan; Amrullah, Hilma; Febriawati, Henni; Yanuarti, Riska (Universitas Airlangga, 2023)
The Government of Indonesia through the National Population and Family Planning Board has established the programme to raise the age of first marriage. Based on the Performance and Accountability Program Survey/Survei Kinerja dan Akuntabilitas Program(SKAP) in 2019, there were 33% of teenagers in Indonesia did not know when to get married. The 2017 IDHS data shows 12,9% that women in Bengkulu have given birth and are pregnant with their first child aged 15-19 years. The cross-sectional study design used secondary data from the 2019 SKAP. Samples of this study were 341 teenager in Bengkulu Province. The instrument was instrument used in SKAP 2019, namely questionnaire for adolescents, families and women of childbearing age which consist of plan of age at first marriage. Analysis data univariable, analysis bivariable chi-square, and analysis multivariable logistic regression. The results showed that the majority of adolescents in Bengkulu Province (71.6%) had plans to marry at the age of 21 for girls and 25 for boys. The predisposing factors related to plan of age at first marriage are adolescent age, adolescent education, adolescent knowledge (Family Development, Family Planning, Adolescent Reproductive Health, Center for Information and Counseling-Adolescent Reproductive Health (PIK-KRR), family planning methods, the Planning Generation (GenRe) Program, impact of Early Marriage), Family Function Practice, Adolescent Attitudes (age of marriage, desire to have children), dating experience and sexual behavior. The most influential factor in the planning of the age at marriage among adolescents in Bengkulu Province is knowledge of reproductive health.